Endemicity Of Toxoplasma Gondii Infections Among Aborted Women in Erbil, The Kurdistan Region of Iraq - Shakar A. Mohammed; Kareem Kh. Hamad (QALAAI ZANIST JOURNAL, 2023)
The current seroprevalence survey was carried out to evaluate the endemic status of Toxoplasma (T.) gondii, which is deemed a ubiquitous zoonotic protozoan pathogen among aborted women in Erbil, the Kurdistan region of Iraq. To meet the requirements of the study, the sera of 270 miscarried women, who attended the emergency department of Maternity Teaching hospital-Erbil from October 20, 2021, to May 1, 2022, were examined serologically using enzyme-linked immunosorbent assay (ELISA). The study revealed that 27.03% of aborted individuals had an inactive infection (IgG), whilst 0.74% of them were harbours of active infections (IgM). The highest percentage of inactive infection (36.19%) was recorded in the age group 31-40 years, whilst the lowest percentage (17.64%) was recorded in the age group 14-20 years. Regarding active infections, a very low percentage (less than 1%) was recorded. Concerning recurrent abortions, there was a significant difference (P<0.05) between various age groups, but there was no significant difference (P>0.05) pertaining to the concentrations of IgG in their sera. The pregnant women in the first trimester were exposed to abortion (86.66%) more than those in the second trimester (13.33%). The highest percentage (57.7%) of abortions was recorded in women with an elementary level of education, while 19.25% and 22.96% of abortions were recorded for illiterate and university levels, respectively. Ultimately, it could be extracted that Toxoplasmosis is still reckoned a threat to the community of pregnant women in the Kurdistan region of Iraq.